Evaluation and mitigation methods for virtual reality motion sickness(面向虚拟现实晕动症的评估与缓解方法) - 顾展滔(GU Zhantao); 丁玎(DING Ding); 陈亦婷(CHEN Yiting); 张文杰(ZHANG Wenjie) (Zhejiang Daxue xuebao. Lixue ban)
Motion sickness is one of the significant factors limiting the development of virtual reality technology. Current research on mitigating virtual reality motion sickness approaches are relatively singular solutions that seldom consider the impact of consistency between virtual and real motion states. To explore the effects of different motion sickness mitigation solutions under conditions of both consistent and inconsistent virtual-real motion, this study implemented three motion sickness mitigation approaches in a virtual reality setting: field of view restriction, peripheral blurring, and visual simplification. Based on these, three mitigation schemes were designed. By collecting subjective and physiological data from 30 participants, the effectiveness of different mitigation solutions under various motion states was evaluated. The findings indicate that under both consistent and inconsistent motion conditions, different mitigation schemes vary significantly in their effectiveness in alleviating virtual reality motion sickness, providing insights for better resolution of motion sickness issues in virtual reality technology.(晕动症是制约虚拟现实技术发展的重要因素之一。目前，针对虚拟现实晕动症的研究方法大多相对单一，且很少考虑虚实运动状态一致性对晕动症的影响。为探索虚拟现实体验过程中虚实运动一致与不一致情况下不同晕动症缓解方案的效果，在虚拟现实场景中设计了视觉范围限制、边缘模糊和视觉简化3种晕动症缓解方案。通过收集30名被试的主观评价数据和客观生理数据，评估了不同缓解方案在不同运动状态下的缓解效果。结果表明，在虚实运动一致和不一致情况下，不同缓解方案对虚拟现实晕动症缓解效果存在显著差异，这为缓解虚拟现实技术中的晕动问题提供了解决思路。)